Penerimaan Teknologi, Iklan, dan Cashback Pengaruhnya Pada Minat Pembelian Ulang - Ferrynela Purbo Laksono; Della Vilia Sari; Rubiyatno R (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The purpose of the study are: 1) analyzing technology acceptance indicators, perceived advertisement, and perceiving of cashback simultaneously influence to repurchase intention, 2) analyzing technology acceptance indicators influences repurchase intention, 3) analyzing perceived advertisement influences repurchase intention, 4) perceiving cashback influences repurchase intention. The population of this research is users of e-wallets especially all OVO users in Yogyakarta. The research used nonprobability sampling. Data was collected by distributing questionnaires. The process of obtaining data got 100 respondents. The data analysis technique in this research is Multiple Regression Linear Analysis using the SPSS 25 application. The results of the study are: 1) technology acceptance indicators, perceived advertisement, and perceived cashback simultaneously influenced repurchase intention, 2) technology acceptance indicators partially influenced the repurchase intention of OVO user, 3) perceived advertisement partially influenced the repurchase intention of OVO user, 4) cashback partially influenced repurchase intention of OVO user.